Therapeutic Effect of Avocatin B in Avocados Toward Acute Myeloid Leukemia - Dias Rima Sutiono; Anthony Ryan Pantoni (Cermin Dunia Kedokteran, 2018)
Acute myeloid leukemia is the abnormal division of immature myeloid precursor cells in the bone marrow affecting mostly older people. Till date, there are no potent treatments due to the fact that it cannot target leukemic stem cells which are responsible for relapse and initiation of leukemia. Current treatments can also pose side effects that might to be too harsh for older people. Avocatin B is a lipid derived from avocado that can be a novel potent drug to replace or go along with the current therapies. Avocatin B is able to induce leukemic cell death and their stem cells while leaving normal cells unharmed. Their mechanisms of actions include inhibiting fatty acid oxidation which causes reactive oxygen species mediated apoptosis and lipotoxicity. Their selectivity towards leukemic cells over normal cells are due to the fact that they are able to target leukemic mitochondria which are different from the normal cells’ mitochondria in terms of their metabolic pathways.Leukemia myeloid akut merupakan sel precursor myeloid dalam sumsum tulang dewasa yang abnormal. Hingga saat ini, belum ada terapi yang tepat untuk leukemia myeloid akut. Avocatin B adalah lipid yang berasal dari alpukat, dapat menjadi obat baru atau digabungkan dengan terapi saat ini. Avocatin B mampu menginduksi kematian sel leukemia dan sel induknya. Mekanisme Avocation B meliputi penghambatan oksidasi asam lemak yang menyebabkan oksigen reaktif memediasi apoptosis dan lipotoksisitas. Selektivitas avocatin B terhadap sel-sel leukemia karena dapat menarget mitokondria penderita leukemia yang berbeda jalur metabolisme dari mitokondria sel-sel normal.